Mutual influence of heart failure on the course of type 2 diabetes mellitus (Texas Journal of Medical Science, 2022)
Chronic heart failure (CHF) is one of the most significant medical and social pathologies characterized by a high prevalence and mortality. According to experts, CHF in Western countries occurs in 1-2% of the general population, reaching 10% in people over 70 years of age. In the Russian Federation, CHF is diagnosed in 7–10% of cases, while more than 65% of Russian patients are people over 60 years old. In the structure of mortality from diseases of the circulatory system, CHF occupies one of the leading positions [9, 13, 15, 16].Among the reasons leading to the development of CHF, arterial is traditionally considered -hypertension (AH) and coronary heart disease (CHD), which occupy the largest share in the structure of nosologies that cause the formation of heart failure (95.5% and 69.7%, respectively). The classical causes of CHF (heart defects, cardiomyopathies , myocarditis, etc.) are less common. At the same time, one of the frequent and significant diseases characterized by the early development of heart failure is type 2 diabetes mellitus (DM), which has been shown in a number of studies.In the Russian Federation, DM ranks third (15.9%) among the causes of CHF [9, 13, 14]. In addition, the occurrence and progression of heart failure in patients with DM is one of the main causes of death in this cohort of patients.